Case report: Evaluation of hindlimb ischemia using 18F-fluorodeoxyglucose positron emission tomography in a cat with cardiogenic arterial thromboembolism - Lee, Hyeongyeong; Lee, Dohee; Kim, Sanggu; Koo, Yoonhoi; Chae, Yeon; Yun, Taesik; Yang, Mhan-Pyo; Kim, Soochong; Kang, Byeong-Teck; Kim, Hakhyun (Frontiers in Veterinary Science, 2023)
A 12-year-old castrated male domestic shorthair cat weighing 6.7 kg presented with acute hindlimb paralysis and tachypnea. The femoral pulse was absent bilaterally. Thoracic radiography showed finding compatible with cardiogenic pulmonary edema. Echocardiography revealed hypertrophic cardiomyopathy phenotype and a spontaneous echocardiographic contrast in the left atrium, suggesting cardiogenic arterial thromboembolism. Oxygen supplementation, diuretics, and antithrombotic and thrombolytic agents were also administered. However, hindlimb motor function was not restored. Severely increased aspartate aminotransferase and creatinine phosphokinase, as well as neutropenia with a degenerative left shift were identified, and amputation was considered to prevent sepsis caused by necrosis of the ischemic tissues. 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography was performed to evaluate the metabolic activity of the muscle tissues and determine the level of amputation. There was no 18F-FDG uptake in the extremities of either the hind limbs or the caudal parts of the bilateral femoral muscle mass, suggesting a loss of metabolic activity in the area. Considering the wide affected area, a decreased quality of life was predicted postoperatively, and the cat was euthanized at the owner's request. Postmortem muscle biopsy confirmed weak atrophy of the left femoral muscle and prominent atrophy of the right calf. This case report describes the use of 18F-FDG PET in a cat with ischemia caused by cardiogenic arterial thromboembolism.